Small sample size and group homogeneity: a crucial ingredient to inter-group bias - Ziegler, Johannes; Fiedler, Klaus (Personality and social psychology bulletin, 2024)
Applying a recently developed framework for the study of sample-based person impressions to the level of group impressions resulted in convergent evidence for a highly robust judgment process. How stimulus traits mapped on the resulting group impressions was subject to two distinct moderators, diagnosticity of traits, and the amplifying impact of early sample truncation. Three indices of diagnosticity—negative valence, extremity, and distance to other traits in a density framework—determined participants’ decision to truncate trait sampling early and hence the final group judgments. When trait samples were negative and extreme and when the distance between high-density traits was small, early truncation of the trait samples fostered high group homogeneity and polarized impressions. Granting that mental representations of in-groups and out-groups rely on systematically different samples, our sampling approach can account for various inter-group biases: out-group homogeneity, out-group polarization and (because negative traits are more diagnostic) out-group derogation.